2017
DOI: 10.1002/anie.201704073
|View full text |Cite
|
Sign up to set email alerts
|

Stable Heterometallic Cluster Ions based on Werner's Hexol

Abstract: Large aqueous ions are interesting because they are useful in materials science (for example to generate thin films) but also because they serve as molecular models for the oxide-aqueous mineral interface where spectroscopy is difficult. Here we show that new clusters of the type M[(μ-OH) Co(NH ) ] (NO ) (M=Al, Ga) can be synthesized using Werner's century-old cluster as a substitutable framework. We substituted Group 13 metals into the hexol Co[(μ-OH) Co(NH ) ] ion to make diamagnetic heterometallic ions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Using am etal nitrate salt to effect the dissociation of the carbonato ligand could also make this approach applicable to the incorporation of other metal ions,given the acidic nature of most metal nitrate salts.A lthough only Group 13 metal ions were tested here,i ti st hought that this approach could apply to any metal acidic enough to affect the dissociation of the carbonato ligand.Thed ata from single-crystal XRD shows that the aluminum analog adopts as imilar structure as the original hexol cluster that contained only cobalt. [17,18] At the center is as ixcoordinate Al 3+ ion, bound with bridging hydroxide ligands that connect it to the outer [Co(NH 3 ) 4 ] 3+ units.T he -NH 3 ligands are split into two chemical environments:either cis to bridging hydroxide ligands or trans to the hydroxide ligands, which can be distinguished in solution (see below). The overall charge on the cluster is balanced with six outer-sphere nitrate ions (Figure 1).One advantage of preparing clusters with diamagnetic Co III and Al III ions is the use of 1 H-NMR and DOSY to understand their solution behavior.T he spectrum obtained for the hexol-type clusters was surprisingly simple,w hich indicated that apure species with high symmetry was present in solution.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Using am etal nitrate salt to effect the dissociation of the carbonato ligand could also make this approach applicable to the incorporation of other metal ions,given the acidic nature of most metal nitrate salts.A lthough only Group 13 metal ions were tested here,i ti st hought that this approach could apply to any metal acidic enough to affect the dissociation of the carbonato ligand.Thed ata from single-crystal XRD shows that the aluminum analog adopts as imilar structure as the original hexol cluster that contained only cobalt. [17,18] At the center is as ixcoordinate Al 3+ ion, bound with bridging hydroxide ligands that connect it to the outer [Co(NH 3 ) 4 ] 3+ units.T he -NH 3 ligands are split into two chemical environments:either cis to bridging hydroxide ligands or trans to the hydroxide ligands, which can be distinguished in solution (see below). The overall charge on the cluster is balanced with six outer-sphere nitrate ions (Figure 1).One advantage of preparing clusters with diamagnetic Co III and Al III ions is the use of 1 H-NMR and DOSY to understand their solution behavior.T he spectrum obtained for the hexol-type clusters was surprisingly simple,w hich indicated that apure species with high symmetry was present in solution.…”
mentioning
confidence: 53%
“…Thed ata from single-crystal XRD shows that the aluminum analog adopts as imilar structure as the original hexol cluster that contained only cobalt. [17,18] At the center is as ixcoordinate Al 3+ ion, bound with bridging hydroxide ligands that connect it to the outer [Co(NH 3 ) 4 ] 3+ units.T he -NH 3 ligands are split into two chemical environments:either cis to bridging hydroxide ligands or trans to the hydroxide ligands, which can be distinguished in solution (see below). The overall charge on the cluster is balanced with six outer-sphere nitrate ions (Figure 1).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…NMR spectroscopy was extensively used to investigate diamagnetic polynuclear species, among which Werner's hexols [22] and Group 13 complexes. [11,12,14] A freshly prepared solution of 1 4-Py • EtOH in C 6 D 6 affords a very rich and well-resolved 1 H NMR spectrum (Figure 3 and Figures S2-S8).…”
Section: Nmr Spectramentioning
confidence: 99%
“…Heteronuclear variants were also accessed. [22][23][24] Of special interest are complexes with formula [Fe III 3 M III (L R ) 2 (dpm) 6 ],…”
Section: Introductionmentioning
confidence: 99%